Pergeseran Struktur Ekonomi dan Potensi Sektor Ekonomi Kabupaten Manggarai Periode 2010-2015 - Ramda, Eduardo Edwin; Utama, Made Suyana (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2017)
Manggarai Regency is an area with their economy potential diverse , but their economic structure starting diverted. This study aim’s to analyze economic structure shifting, leading sectors, and the contribution of the economy on the future. This research used secondary data obtained from the Central Bureau of Statistics of Nusa Tenggara Timur Province and Manggarai Regency started from 2010 until 2015 by using Typologies Klassen analysis, Location Quotioent (LQ), Ratio Growth Model (MRP), Overlay, Shift Share, and Projection with Shift Share approach. Result of research in general shown us that leadings sectors in kabupaten manggarai were mining and quarrying sector; government administrative, defense, and social security compulsory sector; and information and communication sector. Manggarai Regency economic structure has shifted because a change the contribution of the economy to the sector primary to the tertiary sector based on shift share analysis.GDRP of Manggarai Regency on 2016 are Rp. 2.796.281.870.000,00.
Keywords: pergeseran struktur ekonomi; sektor unggulan; proyeksi PDRB.